Proceedings of the 4th Workshop on Argument Mining 2017
DOI: 10.18653/v1/w17-5115
|View full text |Cite
|
Sign up to set email alerts
|

Unit Segmentation of Argumentative Texts

Abstract: The segmentation of an argumentative text into argument units and their nonargumentative counterparts is the first step in identifying the argumentative structure of the text. Despite its importance for argument mining, unit segmentation has been approached only sporadically so far. This paper studies the major parameters of unit segmentation systematically. We explore the effectiveness of various features, when capturing words separately, along with their neighbors, or even along with the entire text. Each su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 23 publications
2
53
0
2
Order By: Relevance
“…A (B) label denotes that the token is at the beginning of an argumentative unit, an (I) label that it lies inside a unit and an (O) label that the token is not part of a unit. This framework has been applied previously for the same task (Stab, 2017;Eger et al, 2017;Ajjour et al, 2017). The architectures proposed in this section build on Ajjour et al (2017), omitting the second Bi-LSTM, which was used to process features other than word embeddings (see section 3.1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A (B) label denotes that the token is at the beginning of an argumentative unit, an (I) label that it lies inside a unit and an (O) label that the token is not part of a unit. This framework has been applied previously for the same task (Stab, 2017;Eger et al, 2017;Ajjour et al, 2017). The architectures proposed in this section build on Ajjour et al (2017), omitting the second Bi-LSTM, which was used to process features other than word embeddings (see section 3.1).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Eger et al (2017) reported different Long short-term memory (LSTM) (Hochreiter and Schmidhuber, 1997) architectures. Further, Ajjour et al (2017) proposed a setup with three bidirectional LSTMs (Bi-LSTMs) (Schuster and Paliwal, 1997) in total as their best solution.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…as a second step, or as a multi-class one, where identification of argumentative units and their classification into claims and premises are performed as a single step. Typically the granularity of this task is coarse, with most approaches considering sentences as the smallest argumentative unit (Florou et al, 2013;Moens et al, 2007;Song et al, 2014;Swanson et al, 2015), although some works focused on the most difficult task of detecting units at the clause level (Park and Cardie, 2014;Goudas et al, 2014Goudas et al, , 2015Sardianos et al, 2015;Stab, 2017;Ajjour et al, 2017;Eger et al, 2017). According to a recent survey (Lippi and Torroni, 2015a), the performance of proposed approaches depends on highly engineered and sophisticated, manually constructed, features.…”
Section: Introductionmentioning
confidence: 99%